Food system financing vulnerability index - Ulimwengu, John M. (International Food Policy Research Institute, 2024)
Food systems are integral to ensuring access to sustainable healthy diets for all, thereby supporting public health, livelihoods, and environmental sustainability. However, these systems are increasingly vulnerable to a range of shocks and stressors, from economic downturns and financial constraints to the impacts of cli mate change and pandemics. One of the most critical determinants of food system resilience is the ability to effectively manage financing vulnerabilities. Financing vulnerability refers to the susceptibility of food system components to performance degradation due to inadequate, inefficient, or uneven allocation of financial re sources. Addressing this issue is paramount for enhancing the system’s capacity to withstand and recover from disruptions while maintaining functionality.